Implementasi Pendidikan Karakter di SD/MI - Rahmat Kamal (Madaniyah, 2014)
The basic concept of character education as well as its implementation at the Elementary School (SD) / Madrasah Ibtidaiyah (MI) level with various characteristics of the psychological development of students in the SD / MI environment is certainly different from the psychological development of students at the next level. Character education becomes very important to be discussed in view of the nation's moral condition which is increasingly apprehensive. Education has a big role and responsibility in solving all national problems, especially problems related to the character of the nation itself. Therefore, character education must be able to become the spirit of the overall education mission and must continue to be developed in the nation's generation as early as possible. The age of the child is a very vital age in determining the next development, so parents, including educators, should properly equip their children with good character and noble character, so that they are able to become an intelligent, superior, and noble generation in the future. will come. In this article, the scope of the discussion focuses on three things; first, the basic concepts of character education in general; two, the characteristics of elementary / MI students; and the third, is the implementation of character education for elementary / MI students. There needs to be an inspiration for us parents as well as educators to maximize back the education of character and character as early as possible, the hope is none other than that our children grow up to be intelligent individuals not only intellectually but also morally and socially.